Complex complicity: A practice note from a woman of colour on the frontline - Rashid, Mariam (Probation journal, 2022)
I work as a Probation Officer; I have been doing this job for almost 15 years. I work primarily with men and have worked in major cities in England. I am a minority in England, both ethnically and religiously. I am a woman, and my family are migrants from Africa, and their grandparents were indentured labour from India. In all the ways I am different, I also often share histories of migration, of minority experience and of being an outsider with many of those I work with. This is the conversation I have with myself most mornings: Can you consider yourself an activist? I ask myself. Can you call yourself an activist, an anti-racist whilst working within this criminal justice system? Can you continue in this work and not betray yourself, your Muslim-ness, your brown-ness, your working class-ness, your immigrant-ness?